Achieving Fast Charge Separation by Ferroelectric Ultrasonic Interfacial Engineering for Rapid Sonotherapy of Bacteria‐Infected Osteomyelitis. Issue 13 (19th February 2023) - Li, Jianfang; Liu, Xiangmei; Zheng, Yufeng; Cui, Zhenduo; Jiang, Hui; Li, Zhaoyang; Zhu, Shengli; Wu, Shuilin
Abstract: Bacteria‐infected osteomyelitis is life‐threatening without effective therapeutic methods clinically. Here, a rapid and effective therapeutic strategy to treat osteomyelitis through ferroelectric polarization interfacial engineering of BiFeO3 /MXene (Ti3 C2 ) triggered by ultrasound (US) is reported. Under US, the ferroelectric polarization induces the formation of the piezoelectric field. US cavitation effect induced sonoluminescence stimulates BiFeO3 /Ti3 C2 to produce photogenerated carriers. With synergistic action of the polarization electric field and Schottky junction, BiFeO3 /Ti3 C2 accelerates the separation of electrons and holes and simultaneously inhibits the backflow of electrons, thus improving the utilization of polarized charges and photogenerated charges and consequently enhancing the yield of reactive oxygen species under US. As a result, 99.87 ± 0.05% of Staphylococcus aureus are efficiently killed in 20 min with the assistance of ultrasonic heating. The theory of ferroelectric ultrasonic interfacial engineering is proposed, which brings new insight for developing ferroelectric ultrasonic responsive materials used for the diagnosis and therapy of deep tissue infection and other acoustoelectric devices. Abstract : The construction of ferroelectric polarization interfacial engineering of BiFeO3 /Ti3 C2 to treat osteomyelitis under ultrasound is reported. The ferroelectric polarization induces the formation of a piezoelectric field. US cavitation effect induced sonoluminescence stimulates BiFeO3 /Ti3 C2 to produce photogenerated carriers. With synergistic action of the polarization electric field and Schottky junction, BiFeO3 /Ti3 C2 enhances the utilization of polarized charges and photogenerated charges, enhancing the yield of reactive oxygen species.